Lymph node metastasis and pattern of recurrence in clinically early stage endometrial cancer with positive lymphovascular space invasion - Mahdi, Haider (J Gynecol Oncol, 2015)
OBJECTIVE: To investigate the rate, predictors of lymph node metastasis (LNM) and pattern of recurrence in clinically early stage endometrial cancer (EC) with positive lymphovascular space invasion (LVSI). METHODS: Women with clinically early stage EC and positive LVSI 2005 to 2012 were identified. Kaplan-Meier curves and logistic regression models were used. RESULTS: One hundred forty-eight women were identified. Of them, 25.7% had LNM (21.7% pelvic LNM, 18.5% para-aortic LNM). Among patients with LNM who had both pelvic and para-aortic lymphadenectomy, isolated pelvic, para-aortic and both LNM were noted in 51.4%, 17.1%, and 31.4% respectively. Age and depth of myometrial invasion were significant predictors of LNM in LVSI positive EC. Node positive patients had high recurrence rate (47% vs. 11.8%, p<0.05) especially distant (60.9% vs. 7.9%, p<0.001) and para-aortic (13.2% vs. 1.8%, p=0.017) recurrences compared to node negative EC. LNM was associated with lower progression-free survival (p=0.002) but not overall survival (p=0.73). CONCLUSION: EC with positive LVSI is associated with high risk of LNM. LNM is associated with high recurrence rate especially distant and para-aortic recurrences. Adjuvant treatments should target prevention of recurrences in these areas.